Materials Theory - El-Azab, Anter
Materials Theory publishes outstanding, original research articles, review articles, letters to the editor, and rapid communications in all areas of theoretical materials science and related computational methods. The scope of the journal covers problems of mechanics, physics, and chemistry of all forms of materials (metals and alloys, ceramics, polymers, functional and biological materials) at all scales and concerning the structure, synthesis, and design and performance of materials, including materials under extreme conditions. Containing novel theoretical concepts, models, and/or mathematical and computational formalisms that advance the state-of-the-art is an essential factor in accepting manuscripts submitted to Materials Theory.